Bibliometric analysis of the scientific production on coastal communities’ social vulnerability to climate change and to the impact of extreme events - Lima, Cibele Oliveira; Bonetti, Jarbas (Natural hazards (Dordrecht), 2020)
Bibliometric analysis is a quantitative evaluation method for scientific research aiming at measuring knowledge expressed as scientific publications in a given field. This paper proposes to analyze the worldwide scientific production on social vulnerability of coastal populations through six bibliometric indicators: typology, historical evolution, geographic distribution, main sources, relevant authors and publications and recurring keywords. The research theme was chosen given the continuous increase of studies related to climatic changes and their consequences to populations in coastal zones. In total, 191 indexed documents covering the period from 1991 to 2019 were selected from the Scopus database, after the examination of more than 900 entries, and analyzed through VOSViewer software and the Bibliometrix R package. The results obtained confirmed the exponential growth of scientific production on this subject. Most frequently impacts considered were coastal flooding and erosion triggered by extreme events and the majority of studies have been presented as academic articles published in scientific journals. Moreover, most documents identified were site-specific, based on secondary data and associated with authors from the USA and the UK, with an emerging production related to authors from developing economies in recent years. Among the 658 authors found, only nine have published three or more articles on the theme, with citations highly concentrated in only four publications. The analysis also revealed the evolution of preferred keywords over time and the lack of consensus in the use of terminology. Studies about coastal social vulnerability were initially mostly focused on the evaluation of risks and exposure to hazards, evolving over time such that the focus shifted to adaptation measures seeking to minimize impacts from climate change to coastal zones.